Dacus تأثير بعض العوامل الاحيائيو والكيميائيو في مكافحة ذبابة القرعيات الكبرى على نبات البطيخ في ) Diptera : Tephritidae ( Iongistylus (Wiedeman) البصره: Influence of Biological and Chemical Factors in big cucumber fly Dacus lonigistylus(wideman) (Tephritidae : Diptera )on melons plant in some Areas of the province of Basrah - الوائلي ضياء سالم (University of Thi-Qar Journal of Science, 2014)
This study was aimed to evalute the efficiency of Biological control agents Beauveria bassiana and Bacillus thuringiensis and 10% Diazinon lnsecticide to Control the big Cucumber fly Dacus lonigstylus on melon plant. Theresult showed that the effect of treatment Diazinon 10 %+ B.t + B.b , Diazinon 10 % + B.b , Diazinon 10 % + B.t, Diazinon 10 % ) gave high mortality of pupae that reach 100 % comparing with other treatment in the lab . The result showed also significant different between the treatment of Bacteria and Fungal suspension on the adult insects in lab.the percentage of infaction where 73.33 و 63.33% respectively during 48 hrs, while there is no significant difference between them in the farm which there percentage of the infection will %13.3و% 10. While the treatment B.t + B.b +Diazinon , B.t + Diazinon , B.b +Diazinon , Diazinon and B.t + B.b gave less lnfection rate that reach 3.3 , 3.3, 3.3 , 6.7 and 10 % respectively comparing with 26.7 % of control treaement in the farm.